Gay guys using gay language: friendship, shared values and the intent‐context‐effect matrixth. (14th July 2016) - McCormack, Mark; Wignall, Liam; Morris, Max
Abstract: This article draws on in‐depth interviews with 35 openly gay male undergraduates from four universities in England to develop an understanding of the changing nature of language related to homosexuality. In addition to finding a diminution in the prevalence of homophobic language, we demonstrate that participants maintain complex and nuanced understandings of phrases that do not use homophobic pejoratives, such as 'that's so gay'. The majority of participants rejected the notion that these phrases are inherently homophobic, instead arguing that the intent with which they are said and the context in which they are used are vital in understanding their meaning and effect. We conceptualize an intent‐context‐effect matrix to understand the interdependency of these variables. Highlighting the situated nature of this matrix, we also demonstrate the importance of the existence of shared norms between those saying and hearing the phrase when interpreting such language.